Macular pigment optical density and its determinants in a Russian population: the ural eye and medical study - Bikbov, Mukharram; Gilmanshin, Timur R.; Zainullin, Rinat M.; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Arslangareeva, Inga I.; Zinnatullin, Ainur A.; Gilemzianova, Leisan I.; Khakimov, Dinar A.; et al. (Acta ophthalmologica, 2022)
Purpose To assess the macular pigment optical density (MPOD) and its associations with ocular and systemic parameters and diseases. Methods The population-based study Ural Eye and Medical Study included 5899 (80.5%) out of 7328 eligible individuals. As part of ophthalmological and systemic examinations, MPOD was measured by reflectometry. Results Macular pigment optical density (MPOD) data were available for 4889 (82.9%) individuals (mean age:57.8 ± 10.1 years;range: 40-94). Mean values for MOPD, maximal MOPD, macular pigment (MP) area and MP volume were 0.13 ± 0.04 d.u. (density units), 0.36 ± 0.09 d.u., 60 791 ± 14 826 pixel and 8033 ± 2888 d.u.pixel, respectively. A higher MP density was correlated (regression coefficient r: 0.63) with older age (standardized regression coefficient beta: 0.59; non-standardized regression coefficient B: 0.23; 95% confidence interval (CI): 0.22, 0.23; p < 0.001), female sex (beta: 0.08; B:0.63; 95%CI: 0.44, 0.83; p < 0.001), rural region of habitation (beta: 0.13; B: 1.02; 95%CI: 0.83, 1.22; p < 0.001), lower body mass index (beta: −0.04; B: −0.03; 95%CI: −0.05, 0.01; p = 0.004), lower prevalence of chronic obstructive pulmonary disorder (beta: −0.03; B: −0.43; 95%CI: −0.79, −0.08; p = 0.02), higher erythrocyte sedimentation rate (beta: 0.03; B: 0.01; 95%CI: 0.002, 0.02; p = 0.03), lower leukocyte cell count (beta: −0.04; B: −0.10; 95%CI: −0.16, −0.03; p = 0.003), thinner temporal parafoveal retinal thickness (beta: −0.06; B: −0.01;95%CI: −0.01, −0.003; p < 0.001), thinner central corneal thickness (beta: −0.06; B: −0.006; 95%CI: −0.009, −0.004; p < 0.001), higher prevalence of pseudophakia (beta: 0.09;B:2.08; 95%CI: 1.50, 2.65; p < 0.001) and reticular pseudo drusen (RPD) (beta: 0.03; B: 0.56; 95%CI: 0.13, 0.98; p = 0.01) and lower stage of open-angle glaucoma (beta: −0.03; B: −0.39; 95%CI: −0.74, −0.04; p = 0. 03). Prevalence (p = 0.44; beta: −0.01) and degree (p = 0.70; beta: −0.01) of angle-closure glaucoma, prevalence (p = 0.31; beta: 0.01) of age-related macular degeneration (AMD) without RPD and prevalence (p = 0.95; beta: 0.001) of diabetic retinopathy were not significantly associated with the mean MP density in that model. Conclusions A higher RPD prevalence and lower stage of open-angle glaucoma were ophthalmological disorders associated with a higher MPOD in a multivariable analysis, including parameters of older age, pseudophakia, female sex, rural region, lower body mass index and lower perifoveal retinal thickness.
Gesehen am 22.05.2023